Carbon footprint from dairy farming system: comparison between Holstein and Jersey cattle in Italian circumstances - Dalla Riva, Alessandro; Kristensen, T.; Marchi, Massimo De; Kargo, Morten; Jensen, Just; Cassandro, Martino (Acta Agraria Kaposváriensis, 2014)
Aim of the present study was to estimate the carbon footprint (CF) of milk production at farm gate considering two dairy cattle breeds, Holstein Friesian (HF) and Jersey (JE). Using Italian inventory data the emissions of CO2eq per kg ECM for dairy herds of HF and JE breed were estimated. The results show 0.80 kg CO2eq/kg ECM in JE herd, while 0.96 kg CO2eq/kg ECM in HF herd. The main differences were due to the level of dry matter intake, milk yield and fertility traits. Indeed, JE herd showed a lower milk yield than HF herd, a lower DMI and better fertility, determining less production and consumption of feed and less replacement animals in the herd.
Keywords: carbon footprint; dairy cattle breed; milk production